Carbonate-containing hydroxyapatite synthesized by the hydrothermal treatment of different calcium carbonates in a phosphate-containing solution - Masanobu Kamitakahara; Takuya Nagamori; Taishi Yokoi; Koji Ioku (Journal of Asian Ceramic Societies, 2015)
Carbonate-containing hydroxyapatite (CHA) particles were synthesized by the hydrothermal treatment of calcium carbonates in a phosphate-containing solution. Three types of calcium carbonates were synthesized: aragonite particles with rough surfaces, calcite particles with rough surfaces by heat treatment of aragonite particles with rough surfaces, and aragonite particles with smooth surfaces. The effects of the calcium carbonate crystal phase and morphology on the synthesized CHA were investigated and morphological changes in the formed CHA particles were observed. The reaction rates varied depending on the calcium carbonate crystal phase and morphology and this difference in reaction rates mainly affected the morphology of the synthesized CHA. On the other hand, the carbonate content and lattice constants of formed CHA were almost independent of the calcium carbonate crystal phase and morphology. This is because the equilibrium mainly governed the composition of the synthesized CHA. The characteristics of the starting material were highly important factors in controlling the morphology of the synthesized CHA.